EU FACILITATES NEW RULES FOR CROSS-BORDER MOBILITY OF COMPANIES - Gabriela FIERBINŢEANU; Vasile NEMEŞ (Challenges of the Knowledge Society)
Legal certainty is needed in the Company Law area, and this could be obtained if all the factors act jointly to achieve this aim by introducing division and conversion regulation, improving legal framework on mergers and in this manner create for company law the possibility to interact properly with EU legal framework specially designed to ensure that cross border operations will not be used in abusive way. The proposed Company Law Package by the European Commission which consists of two proposals for Directives amending Directive (EU) 2017/1132:Directive as regards the use of digital tools and processes in company law and Directive as regards cross-border conversions, mergers and divisions will achieve its best results only when both instruments could work together, complementing each other. Online solutions for European businesses so that they cut costs and save time and the choice of where to do business and how to grow or reorganise their businesses for honest entrepreneurs should push for a fairer modern Single Market. For the first time in European Union law, rules are provided for cross border conversions and divisions and the regime of cross border merger is improved, the legal framework being adapted to the economic and social realities.